A screen-printed Ag/AgCl reference electrode with long-term stability for electroanalytical applications. (10th October 2021) - Dawkins, Rebecca C.; Wen, Dingchen; Hart, Judy N.; Vepsäläinen, Mikko
Highlights: Developed a printed, low-cost, flexible thick film Ag/AgCl reference electrode. Integrated KCl electrolyte and PDMS junction improves performance. Comparable potential stability to commercial electrodes in various environments. Minimal potential drift across the substantial working lifetime. Abstract: Low-cost sensor arrays are required to allow for real-time, in-situ electrochemical monitoring using Internet-of-Things (IoT) systems; however, they are currently not practical due to a lack of stable, mass-producible reference electrodes. To solve this problem, in this work we have developed a screen-printed Ag/AgCl true reference electrode with an offset salt reservoir on a flexible substrate for use in disposable, low-cost sensor arrays. A KCl-containing poly(vinyl acetate) ink was prepared as the solid-state electrolyte, and a PDMS junction membrane was deposited to suppress electrolyte leaching. The potentials of the electrodes with and without the electrolyte and junction membranes were measured versus a commercial saturated calomel reference electrode (SCE) in 0.1 M K2 SO4 solution. Potential stability of −45.5 ± 3 mV vs. SCE with low drift was maintained for up to 27 days for electrodes containing both the electrolyte and PDMS layers, compared to less than 1 day without the PDMS junction. The electrodes were found to be stable in solutions at different pH and were also insensitive to most interfering ionic species, including SO4 2−, I −, Br −, Cl −, F −, Li +, Na +, and K +, under continuous potential measurement with an impedance of ∼ 15 kΩ at 106 Hz. The results demonstrate that the present printed reference electrodes are stable for an extended period and therefore well suited for use in electroanalytical systems for high volume IoT applications. Graphical abstract: Image, graphical abstract